Fourier Raman spectroscopy studies of the As₄₀S₆₀-xSex glasses - Stronski, A.V.; Vlček, M.; Oleksenko, P.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The present paper is concerned with the investigations of As₄₀S₆₀-xSex glasses with the help of Fourier Raman spectroscopy. The results of Raman spectroscopy investigations indicate increased presence of non-stoichiometric Sen, As₄S₄ fragments for intermediate compositions of As₄₀S₆₀-xSex glasses, which in combination with composition dependencies of molar volume, previous results on investigations of optical and thermal properties of As₄₀S₆₀-xSex can be explained by the small deviation from the statistical one under the isovalent substitution of Se on S in As₄₀S₆₀-xSex glasses with the composition change.